PW 0456 Intentional self-harm and assault injury hospitalisation characteristics, treatment cost, and health outcomes of children in australia over a 10-year period. (November 2018) - Mitchell, Rebecca J; Seah, Rebecca; Ting, Hsuen P; Curtis, Kate; Foster, Kim
Abstract : Background: Both self-harm and interpersonal violence are leading causes of injury mortality and hospitalised morbidity, with a significant economic and societal cost. Objective: To determine the 10 year temporal trends, treatment cost and health outcomes of intentional injury hospitalisations of children aged ≤16 years in Australia. Method: A retrospective examination of linked hospitalisation and mortality data for children aged ≤16 years during 1 July 2001 to 30 June 2012 with self-harm or assault injuries. Thirty-day mortality and 28 day hospital readmission were calculated. Results: There were 18 223 self-harm and 13 877 assault hospitalisations, with a treatment cost of $64 million and $60.6 million, respectively. The self-harm hospitalisation rate was 59.8 per 1 00 000 population (95% CI 58.96–60.71) with no annual decrease. Poisoning was the most common method of self-harm. The assault hospitalisation rate was 29.9 per 1 00 000 population (95% CI 29.39–30.39) with a 4.2% annual decrease (95% CI −6.14 to −2.31, p<0.0001). Other maltreatment syndromes were common for children≤5 years. Assault by bodily force was common for children 6–16 years. There were 1520 (8.3%) and 654 (4.7%) hospital readmissions within 28 days and 66 (0.4%) and 32 (0.2%) deaths for self-harm and assault injury hospitalisations, respectively. Conclusions: Australia needs a whole-of-government and community approach to prevent intentional injury. Health professionals can play a key role in identifying and preventing the recurrence of intentional injury. Psychosocial care and access to support services are essential for self-harmers. Parental education interventions to reduce assaults of children and training in conflict de-escalation to reduce child peer-assaults are recommended.